Antiphase Boundaries Constitute Fast Cation Diffusion Paths in SrTiO3 Memristive Devices. (16th September 2020) - Heisig, Thomas; Kler, Joe; Du, Hongchu; Baeumer, Christoph; Hensling, Felix; Glöß, Maria; Moors, Marco; Locatelli, Andrea; Menteş, Tevfik Onur; Genuzio, Francesca; Mayer, Joachim; De Souza, Roger A.; et al.
Abstract: Resistive switching in transition metal oxide‐based metal‐insulator‐metal structures relies on the reversible drift of ions under an applied electric field on the nanoscale. In such structures, the formation of conductive filaments is believed to be induced by the electric‐field driven migration of oxygen anions, while the cation sublattice is often considered to be inactive. This simple mechanistic picture of the switching process is incomplete as both oxygen anions and metal cations have been previously identified as mobile species under device operation. Here, spectromicroscopic techniques combined with atomistic simulations to elucidate the diffusion and drift processes that take place in the resistive switching model material SrTiO3 are used. It is demonstrated that the conductive filament in epitaxial SrTiO3 devices is not homogenous but exhibits a complex microstructure. Specifically, the filament consists of a conductive Ti 3+ ‐rich region and insulating Sr‐rich islands. Transmission electron microscopy shows that the Sr‐rich islands emerge above Ruddlesden–Popper type antiphase boundaries. The role of these extended defects is clarified by molecular static and molecular dynamic simulations, which reveal that the Ruddlesden–Popper antiphase boundaries constitute diffusion fast‐paths for Sr cations in the perovskites structure. Abstract : The cation diffusion processes that take place during operation of perovskite memristive devices are investigated. Based on insights from spectromicroscopy and atomistic simulations, the role of extended defects is clarified. It is shown that they play a decisive role in device functionality.